2020
DOI: 10.3390/polym12040971
|View full text |Cite
|
Sign up to set email alerts
|

UV-Casting on Methacrylated PCL for the Production of a Peripheral Nerve Implant Containing an Array of Porous Aligned Microchannels

Abstract: Peripheral nerves are basic communication structures guiding motor and sensory information from the central nervous system to receptor units. Severed peripheral nerve injuries represent a large clinical problem with relevant challenges to successful synthetic nerve repair scaffolds as substitutes to autologous nerve grafting. Numerous studies reported the use of hollow tubes made of synthetic polymers sutured between severed nerve stumps to promote nerve regeneration while providing protection for external fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…The average number of neurites expressed per NG108-15 neuronal cell body was estimated at ~1.4 (Fig. 6C), in line with what has been previously reported using the same NG108-15 cell line on other scaffolds [94,95]. The average number of neurites per neuronal cell body decreased at increased GO content, while no differences were observed among the rGO/silk composites.…”
Section: Neuronal Differentiationsupporting
confidence: 89%
“…The average number of neurites expressed per NG108-15 neuronal cell body was estimated at ~1.4 (Fig. 6C), in line with what has been previously reported using the same NG108-15 cell line on other scaffolds [94,95]. The average number of neurites per neuronal cell body decreased at increased GO content, while no differences were observed among the rGO/silk composites.…”
Section: Neuronal Differentiationsupporting
confidence: 89%
“…A previous study from our group also highlighted the cytocompatibility of similar PCLMA material to that reported in this study. Neuronal and Schwann cells were cultured on PCLMA and shown to exhibit comparable viability compared to TCP controls as assessed via a live/dead assay [ 84 ]. In the same study, porous PCLMA nerve guidance conduits were used to repair rat sciatic nerve injuries and resulted in good tissue integration.…”
Section: Resultsmentioning
confidence: 99%
“…Casting enables the manufacturing of scaffolds in a wide range of shapes and sizes, depending on the mould design ( Paljevac et al, 2018 ; Diez-Ahedo et al, 2020 ; Dikici et al, 2020a ; Owen et al, 2020 ). Recently, Dikici et al (2020a) reported the fabrication of the PolyHIPEs in tubular form by designing a re-usable tubular silicone mould system that, HIPE can be injected into, polymerised, and recovered easily ( Figure 10Ab ).…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%